2019
DOI: 10.5688/ajpe6584
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Interprofessional Medication Therapy Management Experience

Abstract: Objective. To measure the impact of an interprofessional experience (IPE) in medication therapy management (MTM) on students' attitudes and skills regarding interprofessional collaboration (IPC). Methods. This interprofessional MTM experience spanned three weeks, with health science students (medicine, nursing, nutrition, and pharmacy) meeting once weekly. The IPE facilitated interprofessional student collaboration via small-group sessions to conduct MTM consultations for patients with complex chronic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As indicated above, to supplement our list of small group issues, we conducted a short, focused review of articles published in both 2018 and 2019 in health professions education journals. RZ (one of the authors) found 36 articles involving small groups from these journals: (numbers of articles in parentheses): Nurse Education Today (9), BMC Medical Education (9), Journal of Nursing Education (8), America Journal of Pharmaceutical Education (7), Academic Medicine (1), Journal of Veterinary Medical Education (1), and Journal of Dental Education (1). MD summarized the descriptions of how the groups in these studies were organized and facilitated into the five elements of CL.…”
Section: Résumémentioning
confidence: 99%
“…As indicated above, to supplement our list of small group issues, we conducted a short, focused review of articles published in both 2018 and 2019 in health professions education journals. RZ (one of the authors) found 36 articles involving small groups from these journals: (numbers of articles in parentheses): Nurse Education Today (9), BMC Medical Education (9), Journal of Nursing Education (8), America Journal of Pharmaceutical Education (7), Academic Medicine (1), Journal of Veterinary Medical Education (1), and Journal of Dental Education (1). MD summarized the descriptions of how the groups in these studies were organized and facilitated into the five elements of CL.…”
Section: Résumémentioning
confidence: 99%
“…Interprofessional rotations are shown to improve students' educational experience and patient satisfaction with patient care. It is feasible and productive (Schussel et al, 2019). Students value participation in interprofessional rotations (Jebara et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this pharmacokinetic simulation, nursing students conduct a head-to-toe assessment and pharmacy students collect the necessary information and data from the results of the nurse's assessment and calculate the required dose. This is supported by the research of Schussel (Schussel, Forbes, Taylor, & Cooley, 2019). This study carried out the implementation of IPE by means of Medication Therapy Management (MTM).…”
mentioning
confidence: 99%